ANALISIS POLA KEMISKINAN MASYARAKAT NELAYAN DI KELURAHAN BANTAYA - Kaliongga, Feybe Georgianna (Katalogis, 2017)
This research aims to analyze the poverty pattern and the factors that cause poverty of fishermen society of Bantaya Sub-district. This research was a descriptive research using mixed method as data analysis. The results of the research showed that: 1) Poverty patternÂ is formed of the fishermen society in Bantaya Sub-district namely: Subsistence poverty, Protection of poverty, and poverty of understanding; 2) Factors that cause poverty are internal factors (intellectual factors, mental factors, psychological factors, skill factors, asset factors) and external factors (land ownership factors).